A Frequency-Tracking and Impedance-Matching Combined System for Robust Wireless Power Transfer - Yanting Luo; Yongmin Yang; Suiyu Chen; Xisen Wen (International Journal of Antennas and Propagation)
One of the greatest challenges to power embedded devices using magnetically coupled resonant wireless power transfer (WPT) system is that the amount of power delivered to the load is very sensitive to load impedance variations. Previous adaptive impedance-matching (IM) technologies have drawbacks because adding IM networks, relay coils, or other compensating components in the receiver-side will significantly increase the receiver size. In this paper, a novel frequency-tracking and impedance-matching combined system is proposed to improve the robustness of wireless power transfer for embedded devices. The characteristics of the improved WPT system are investigated theoretically based on the two-port network model. Simulation and experimental studies are carried out to validate the proposed system. The results suggest that the frequency-tracking and impedance-matching combined WPT system can quickly find the best matching points and maintain high power transmission efficiency and output power when the load impedance changes.